Study on unsteady diffusion characteristics of primary coal and tectonic coal under the influence of pressure and particle size - Shouqing LU; Lurui TAN; Yujin QIN; Zhanyou SA; Jie LIU; Yongliang ZHANG (Meikuang Anquan)
In order to further study the characteristics of gas desorption and diffusion in coal, the gas desorption and diffusion experiments of primary coal and tectonic coal with different gas pressures (0.8, 1.3, 2.4, 3.3 MPa) and different particle sizes (0.074-0.250, 0.250-0.500, 0.500-1.000, 1.000-3.000 mm) were carried out. The effects of pressure and particle size on gas desorption and gas desorption rate in primary coal and tectonic coal were discussed. The unsteady diffusion model of gas was established and the unsteady diffusion characteristics of coal samples were analyzed. The main conclusions are as follows: the gas desorption amount of primary coal and tectonic coal increases with the increase of pressure. The growth rate of gas desorption amount of primary coal with the increase of pressure is larger than that of tectonic coal, which leads to the decrease of the total gas desorption amount gap between the two. The gas desorption amount of primary coal and tectonic coal increases with the decrease of particle size. The decrease of particle size only changes the growth trend of gas desorption amount of primary coal, but does not change the growth trend of gas desorption amount of tectonic coal. The increase of pressure has little effect on the change of gas desorption rate of primary coal and tectonic coal. The decrease of particle size makes the change trend of gas desorption rate of primary coal change from fast to slow to rapid decrease, but does not make the change trend of gas desorption rate of tectonic coal change. The unsteady diffusion characteristics of tectonic coal gas diffusion coefficient change more obviously with the increase of pressure, while the diffusion characteristics of primary coal gas do not change much. The decrease of particle size can make the gas desorption and diffusion characteristics of primary coal change from steady state to unsteady state, and the decrease of particle size leads to the unsteady characteristics of gas desorption and diffusion of tectonic coal more obvious, but it does not change the essence of unsteady diffusion.